Strengthening The Role of Teachers as Classroom Managers Through The Implementation of The Concept of Education Management at SD Negeri Sumber Harta: Pengabdian - Triono; Rafikha Anggraini; Pika Meri Yanti; Prantiastio; Kris Suspon Rama; Rozie Meidy; Nadia Ulfa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The role of teachers in the educational process is not only limited to the instructional function but also includes a strategic role as a classroom manager responsible for creating a conducive learning environment. This activity aims to enhance teachers' competence in classroom management by promoting the understanding and application of educational management concepts. The methods used in this activity include interactive lectures, group discussions, case studies, simulations, and the preparation of follow-up plans. The results of the activity demonstrated an increase in teachers' understanding of the fundamental principles of educational management, as well as their ability to design and implement effective classroom management strategies. Through this activity, teachers are expected to enhance their role in enhancing the quality of learning and fostering a positive classroom climate. This program is the first step in efforts to improve the quality of education at SD Negeri Sumber Harta through an applicable and sustainable managerial approach